1998
DOI: 10.1021/jm980031t
|View full text |Cite
|
Sign up to set email alerts
|

Noncalcemic, Antiproliferative, Transcriptionally Active, 24-Fluorinated Hybrid Analogues of the Hormone 1α,25-Dihydroxyvitamin D3. Synthesis and Preliminary Biological Evaluation

Abstract: Four new hybrid analogues of 1alpha,25-dihydroxyvitamin D3 (1) have been synthesized in a convergent manner by joining A-ring and C, D-ring fragments. Each hybrid analogue, having a noncalcemic 1-hydroxymethyl group and a potentiating 16-ene 24,24-difluorinated C,D-ring side chain, was designed to be lipophilic and inert toward 24-hydroxylase enzyme catabolism. Each hybrid analogue with 1beta, 3alpha-substituent stereochemistry (i.e., analogues 3b and 4b) showed a pharmacologically desirable combination of in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 34 publications
3
57
1
Order By: Relevance
“…In confirmation of the microarray studies, Fig. 2B further shows that QW was uniquely different from the analogue EB 1089 (26), in that EB 1089 stimulated, rather than decreased, CYP24 message expression.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…In confirmation of the microarray studies, Fig. 2B further shows that QW was uniquely different from the analogue EB 1089 (26), in that EB 1089 stimulated, rather than decreased, CYP24 message expression.…”
Section: Resultssupporting
confidence: 68%
“…The presence of both the 1-a and the 25-hydroxyl groups is generally thought to be essential for effective binding of the 1,25(OH) 2 D 3 ligand to the VDR (25). It has been reported that the newly synthesized hybrid analogue QW-1624F2-2 (QW; prepared by incorporating the calcium ablating 1-hydroxymethyl alteration along with the potentiating C, D ring 16-unsaturation, side chain 24,24-difluorination, and 26,27-homologation) has potent antiproliferative effects in a skin tumor models (26,27), indicating that growth inhibition may not require the 1-a and 25-dihydroxy groups (28). The side chain group may be binding to the nuclear VDR as a hydrogen-bond acceptor, in contrast to the hydrogen-bond donor function of the 25-OH group of natural 1,25(OH) 2 D 3 (29).…”
Section: Introductionmentioning
confidence: 99%
“…The cells were passaged and fed with medium 2-3 times per week to maintain the log phase growth. 1,25D was a kind gift from Dr. Milan Uskokovic, BioXell, Inc., Nutley, NJ., and its analog JKF was synthesized as previously described [17,26]. Carnosic acid (CA) was purchased from Alexis Corporation (San Diego, CA.)…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…One approach to overcome this problem is to design analogs of 1,25D with high potency as differentiation agents, but with reduced calcemia-inducing properties. For instance, the introduction of the D ring 16 unsaturation, and fluorines into the side chain of the seco-steroids, decreases their susceptibility to initiation of degradation by the CYP24 hydroxylase [14][15][16][17], while the introduction of the lα-hydroxymethyl group in the A ring serves to reduce the calcemic properties of the compound [18]. One such synthetic derivative of 1,25D, compound JK-1624F2-2 (JKF), shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although paricalcitol is FDA-approved for treatment of secondary hyperparathyroidism, its mechanisms of action in cancer are still being elucidated. QW is a novel fluorinated hybrid analog of calcitriol that is 100 times less calcemic and inhibits growth of melanoma cells [40]. QW inhibits skin carcinogenesis in vivo [41, 42] without inducing hypercalcemia [41].…”
Section: Introductionmentioning
confidence: 99%